The cellular protein nucleolin preferentially binds long-looped G-quadruplex nucleic acids - Sara Lago; Elena Tosoni; Matteo Nadai; Manlio Palumbo; Sara N. Richter (2016)
G-quadruplexes (G4s) are four-stranded nucleic acid structures that form in G-rich sequences. Nucleolin (NCL) is a cellular protein reported for its functions upon G4 recognition, such as induction of neurodegenerative diseases, tumor and virus mechanisms activation. We here aimed at defining NCL/G4 binding determinants.